RESPONS AMERIKA SERIKAT TERHADAP KEMUNCULAN WIKILEAKS SEBAGAI PEMBOCOR RAHASIA - Fiona Fidela Praba Rukmani (HI 16 UMY 089, 2016)
*89 The mass document publications on WikiLeaks involve imperative questions regarding cyber crime and foreign threat. This paper is concerned to discuss the cyber-security implications since WikiLeaks’ crucial releases only highlighted the well-known case of government espionage, raising larger questions about the aforementioned issues. From this point forward the Government’s response to the various releases can provide a blueprint, but is also a starting point for reviewing their own flaws in the law and orders. In general, the response of the government was framed into (1) a few words by the United States concerning the cyber-security and (2) the confabulation of the releases’ overall impact by WikiLeaks, and will conclusively be closed with a detailed analysis towards (3) the conditions of the government’s response that have occured explicitly due to the threat